2010
DOI: 10.1051/0004-6361/200912641
|View full text |Cite
|
Sign up to set email alerts
|

Stellar interactions in dense and sparse star clusters

Abstract: Context. Stellar encounters potentially affect the evolution of the protoplanetary discs in the Orion Nebula Cluster (ONC). However, the role of encounters in other cluster environments is less known. Aims. We investigate the effect of the encounter-induced disc-mass loss in different cluster environments. Methods. Starting from an ONC-like cluster we vary the cluster size and density to determine the correlation of collision time scale and disc-mass loss. We use the nbody6++ code to model the dynamics of thes… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
92
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 44 publications
(99 citation statements)
references
References 67 publications
7
92
0
Order By: Relevance
“…So the disc-destroying encounters most probably have quite low mass ratios in this environment. This is in accordance with the results of Olczak et al (2010). They found that in clusters of higher density than the ONC the lowmass stars dominate the encounter history, leading to lower encounter mass ratios.…”
Section: Appendix A: Properties Of Disc-destroying Encounterssupporting
confidence: 92%
See 4 more Smart Citations
“…So the disc-destroying encounters most probably have quite low mass ratios in this environment. This is in accordance with the results of Olczak et al (2010). They found that in clusters of higher density than the ONC the lowmass stars dominate the encounter history, leading to lower encounter mass ratios.…”
Section: Appendix A: Properties Of Disc-destroying Encounterssupporting
confidence: 92%
“…Olczak et al 2010;. Before studying this effect on the disc size in an entire star cluster, we first study the influence of a fly-by on a single star-disc system.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations